People’s Perception towards Variability of Climate Change and its Impact on Livestock in Kaski District - Timilsina, Bal Ram; Dhungana, Ananta Raj; KC, Vikash Kumar; Khand, Purna Bahadur (Journal of Development and Social Engineering, 2024)
Climate change is one of the most important issues of the twenty-first century, and understanding climate change its sources, impacts, and potential amelioration is an inherent development concern. This study aims to analyze the people’s perception towards variability of Climate Change and its impact on Livestock in Kaski District. For this purpose, Machhapuchhre Rural Municipality and Ward 19 as well as 20 of Pokhara Metropolitan City and Rupa Rural Municipality were selected for information collection. Information was collected by using a structured questionnaire from 260 respondents with age 45 years and above. A descriptive analysis was carried out for this study. The indicators of variability of climate change were measured in five-point Likert scale. The majority of the respondents perceived the increment in the annual average maximum temperature, while the timing of rainfall, amount of rainfall and the cases of drought incidents have been increased but annual average rainfall has been decreased. The winter as well as the summer annual rainfall has been decreased. Incidence of new diseases in livestock has been increased. The growth of new noxious weed is the most perceived impact of climate change. Summer hotness has increased milk and meat production whereas winter coldness has decreased milk and meat production. There has been decrement in animal and birds’ diversity. Morbidity of the livestock has been increased but the longevity of livestock has been decreased. These findings provide valuable insights into local perceptions, which can guide adaptation strategies and policy interventions.